2002
DOI: 10.1653/0015-4040(2002)085[0102:eoiotc]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Irradiation on the Courtship Behavior of Medfly (Diptera, Tephritidae) Mass Reared for the Sterile Insect Technique

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
0
9

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(131 citation statements)
references
References 19 publications
4
118
0
9
Order By: Relevance
“…Sterile males had reduced pheromone-calling activity compared with fertile males, which may explain why sterile males were less successful in attracting mates. This result is consistent with the observation that sterilization negatively affected male courtship (Papadopoulos et al 1998;Lux et al 2002;but see Liimatainen et al 1997) and pheromone composition (Heath et al 1994).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Sterile males had reduced pheromone-calling activity compared with fertile males, which may explain why sterile males were less successful in attracting mates. This result is consistent with the observation that sterilization negatively affected male courtship (Papadopoulos et al 1998;Lux et al 2002;but see Liimatainen et al 1997) and pheromone composition (Heath et al 1994).…”
Section: Discussionsupporting
confidence: 92%
“…Third, the radiation dose used in SIT programmes varies between 10 and 15 krad (e.g. Lux et al 2002), and higher doses than used in our study could reduce the mating competitiveness of the sterile males even further. Therefore, the poor mating success of sterile males in real SIT programmes represents a more significant problem than shown in our model.…”
Section: Discussionmentioning
confidence: 83%
“…At a constant number of non-treated males in mating trials, egg hatch decreased significantly when a proportion of treated males increased. The observed values of egg hatch were greater than those of expected ones in all variants, however, significant difference (1 df; P < 0.05) was only observed for the 5:1:1 sex ratio Lux et al 2002). In the competitiveness test, we did not use a dose of 90 Gy, because at this dose total sterility was observed and SIT depends on releases of sub-sterilized, not completely sterile males.…”
Section: Flight Ability Testmentioning
confidence: 81%
“…When a female mates with a sterile male, it has no offspring; thus, the next generation's population is reduced. Various studies have shown that although sterile mass-reared medflies do join mating aggregations ('leks'), they are clearly disadvantaged compared with wild males when competing for wild females (McInnis et al, 1996;Lance et al, 2000;Cayol, 2000;Lux et al, 2002). Consequently, there is a need to improve the competitive ability of the released sterile medfly males to enhance the effectiveness of SIT control programs.…”
Section: Introductionmentioning
confidence: 99%